CONTINUOUS GRADATIONS AMONG PRIMARY CARBONATITIC, KIMBERLITIC, MELILITITIC, BASALTIC, PICRITIC, AND KOMATIITIC MELTS IN EQUILIBRIUM WITH GARNET LHERZOLITE AT 3-8 GPA - Gudfinnsson G.H.; Presnall D.C. (My University, 2005)
Multianvil melting experiments in the system CaO–MgO–Al2O3–SiO2–CO2 (CMAS–CO2) at 3–8?GPa, 1340–1800°C, involving the garnet lherzolite phase assemblage in equilibrium with CO2-bearing melts, yield continuous gradations in melt composition between carbonatite, kimberlite, melilitite, komatiite, picrite, and basalt melts. The phase relations encompass a divariant surface in P–T space. Comparison of the carbonatitic melts produced at the low-temperature side of this surface with naturally occurring carbonatites indicates that natural magnesiocarbonatites could be generated over a wide range of pressures >2·5?GPa. Melts analogous to kimberlites form at higher temperatures along the divariant surface, which suggests that kimberlite genesis requires more elevated geotherms. However, the amount of water found in some kimberlites has the potential to lower temperatures for the generation of kimberlitic melts by up to 150°C, provided no hydrous phases are present. Compositions resembling group IB and IA kimberlites are produced at pressures around 5–6?GPa and 10?GPa, respectively, whereas the compositions of some other kimberlites suggest generation at higher pressures still. At pressures <4?GPa, an elevated geotherm produces melilitite-like melt in the CMAS–CO2 system rather than kimberlite. Even when a relatively CO2-rich mantle composition containing 0·15?wt % CO2 is assumed, kimberlites and melilitites are produced by <1% melting and carbonatites are generated by even smaller degrees of melting of <0·5%.